Agenda Setting Al Jazeera dalam Konflik Mesir tahun 2013 : Analisis Peran Media Sebagai Aktor Diplomasi Publik Qatar - Wahyuni, Retno Sri; Utomo, Tri Cahyo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
As active mainstream media in Middle East, News station Al Jazeera TV located in Qatar, often produce propaganda. As result, Al Jazeera TV considered threathening the regime. In fact, the force to close this News Station has been a part of threeten demand of Gulf Country when Qatar diplomatic crisis appeared in 2017. This research, the writer focus on Al Jazeera role in the case of the overthrow of the regime of President Mohamed Morsi in Egypt in 2013. Some of the parties claim that Al Jazeera are neutral in delivering the news in present a new viewpoint for this conflict, while the other party claim Al Jazeera is biased for it is impressed by the Muslim Brotherhood that at the time Against President Mohamed Morsi's regime. This study would explain the role of Al Jazeera TV using a public diplomacy approach. Specifically, the study argued that Al-Jazeera support people at the time it was a form of propaganda in public diplomacy.